Phát triển ngân hàng số tại các ngân hàng thương mại Việt Nam trước bối cảnh cuộc cách mạng công nghiệp 4.0 - Trần Chí, Chinh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
The objective of the article is to analyze the development of digital banking in Vietnamese commercial banks in the context of Industrial Revolution 4.0. To achieve this goal, the author employs a content analysis method based on secondary data collected from the annual reports of Vietnamese commercial banks in 2021. Research results show that Vietnamese commercial banks are at the level of open banking and in the stage of responding to new competition. Therefore, in order to accelerate the diffusion of innovation through digital banking, it is necessary to effectively apply the achievements of Industry 4.0. In order to do so, in addition to the need to have full awareness of digital banking, willingness, and determination to pursue digital transformation, Vietnamese commercial banks need to have appropriate orientations and strategies for digital banking development.